Defending Christ: the Latin apologists before Augustine - Thomas, Nicholas L. (Studia traditionis theologiae, 2011)
"This work is a discussion of the African Latin apologists prior to St. Augustine. The time-frame ranges from the end of the second century into the opening of the fourth [in] one of the most important locations in the formative history of Christian doctrine and practice."--Cover, p. [4]